I am your food system for you to transform - Covic, Namukolo M. (International Livestock Research Institute, 2021)
Namukolo Covic, of the International Food Policy Research Institute (IFPRI), speaks on the role of livestock in sustainable food systems in Africa. This video was produced for the United Nations Food Systems Summit in 2021.